Slavery of the State of Jammu & Kashmir and the Defecto Governance of Azad Kashmir in Its Historical Perspective - Muhammad Ashraf (Journal of Religion and Society, 2025)
Under this research, the State of Jammu and Kashmir as a whole is discussed with brief history that how it has been governed by different tribes under different ways of methodologies, which depicts the importance and culture of this historical state already existed from an im-memorable period. The civilization and culture of the Kashmiri people in its historical perspective have been given a touch in this chapter. In continuance of historical perspective, the constitutional crises based relationship of Azad Jammu and Kashmir territory with Pakistan has also been discussed in a brief way under different circumstances which were and are being faced by the people of Azad Jammu and Kashmir and the people of Pakistan too. The territory of Azad Jammu and Kashmir District-wise have been discussed by throwing a light on the culture, civilizations and nature of the people residing therein. There are three parts of this research paper. In first part, the history of the State of Jammu and Kashmir have been discussed from its ancient Hindu period till the period of the partition of Indian subcontinent 1947. The regimes of Sikhs, Afghans, Mughals etc. have been discussed shortly in order to know that how the people of this State have been treated and governed under multiple cultures and civilizations. The second part of this research solely focused on the territory of Azad Jammu and Kashmir, which is the nucleus of this thesis. The Culture, languages, employment sources etc. of the people of this area have been expressed in District-wise. And the last part of this research deals with the Constitutional relationship of Pakistan and Azad Kashmir in its historical perspective particularly from 1947 to till now that how the people of Azad Jammu and Kashmir are being governed by the Federal Government of Pakistan while performing its functions under UNO resolutions. What different mechanism have been adopted by the Federal Government of Pakistan from 1947 to till now with regard to the good governance in Azad Jammu and Kashmir under different treaties and agreements. Keywords: Slavery, State of Jammu & Kashmir, Defecto Governance, Azad Kashmir, Historical Perspective